2015
DOI: 10.1242/jcs.165365
|View full text |Cite
|
Sign up to set email alerts
|

The prion protein inhibits monocytic cell migration by stimulating β1 integrin adhesion and uropod formation

Abstract: The broad tissue distribution and evolutionary conservation of the glycosylphosphatidylinositol (GPI)-anchored prion protein (PrP, also known as PRNP) suggests that it plays a role in cellular homeostasis. Given that integrin adhesion determines cell behavior, the proposed role of PrP in cell adhesion might underlie the various in vitro and in vivo effects associated with PrP loss-of-function, including the immune phenotypes described in PrP −/− mice. Here, we investigated the role of PrP in the adhesion and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Interestingly, it was demonstrated that PrP C -null mice present increased paracellular permeability, with lower levels of E-cadherin, desmoplakin, occluding, and other proteins related to cell-cell junctions in intestinal tissues [45]. Furthermore, it was reported that PrP C is able to regulate β1 integrin adhesiveness modulating ligand-induced changes in integrin activation [46]; however, its depletion had no effect on total β1 integrin expression levels [47]. These data suggest that PrP C may be capable of recruiting cell adhesion molecules to the cell surface of GSCs, raising the hypothesis of PrP C modulating invasion-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was demonstrated that PrP C -null mice present increased paracellular permeability, with lower levels of E-cadherin, desmoplakin, occluding, and other proteins related to cell-cell junctions in intestinal tissues [45]. Furthermore, it was reported that PrP C is able to regulate β1 integrin adhesiveness modulating ligand-induced changes in integrin activation [46]; however, its depletion had no effect on total β1 integrin expression levels [47]. These data suggest that PrP C may be capable of recruiting cell adhesion molecules to the cell surface of GSCs, raising the hypothesis of PrP C modulating invasion-related processes.…”
Section: Discussionmentioning
confidence: 99%
“… 19,28 Similarly, PrP was found to colocalize with β1 integrins on membrane caps in polarized monocytic cells and to regulate β1 integrin-mediated monocyte adhesion to fibronectin and VCAM-1. 20 PrP-deficient monocytes display a reduced ability to bind polyvalent VCAM-1, without significant alterations in β1 integrin affinity, suggesting that PrP silencing reduces the valency of integrin adhesion. In agreement with the fact that increases in integrin valency are important to resist blood flow shear stress forces, PrP-deficient monocytes displayed reduced firm adhesion to the endothelium under shear flow conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Migrating human monocytic U937 leukocytes plated on immobilized VCAM-1 and CXCL12 acquire a polarized shape consisting of a leading edge followed by the cell body and a rear end formed by the uropod, where b1 integrins and phosphorylated ERM proteins accumulate. 20 …”
Section: Introductionmentioning
confidence: 99%
“…A separate study has proposed that PrP C may regulate human monocyte migration by modulating cell adhesion dynamics [ 52 ]. The authors propose that PrP C regulates β 1-integrin-mediated adhesion by modulating the remodelling of the actin cytoskeleton through the RhoA-cofilin pathway.…”
Section: The Enigmatic Function Of Prp C In Thementioning
confidence: 99%
“…This implies that DC could be manipulated to provide immunotherapeutic protection against prion diseases [ 54 , 106 , 107 ]. (6) The physiological function of cellular PrP C is uncertain but in DC may play a role in the immune synapse or in the regulation of cell migration [ 51 , 52 ].…”
Section: Figurementioning
confidence: 99%